The anti-mycobacterial activity of Lantana camara a plant traditionally used to treat symptoms of tuberculosis in South-western Uganda - Kirimuhuzya, Claude; Waako, Paul; Joloba, Moses; Odyek, Olwa (African health sciences, 2009)
Tuberculosis continues to be a devastating public health problem. Many communities in Uganda use medicinal plants to treat various infections, including respiratory tract infections. There are claims that some can treat tuberculosis. Verifying some of these claims could lead to discovery of lead compounds for development of a TB drug. Methods: Chloroform and methanol extracts of L. camara collected from South-western Uganda were screened against three strains of Mycobacterium tuberculosis using the agar-well diffusion method. H37Rv, the rifampicin-resistant TMC-331 and a non-resistant wild strain (28-25271). The MIC and MBC were determined using the Agar dilution method on Middle brook 7H11. Results: The methanol extract showed the highest activity against all the three strains used, with zones of inhibition of 18.0-22.5 mm and MIC values of 20 μg/ml for H37Rv and 15 μg/ml for both TMC-331 and wild stain. The values for rifampicin were 1.0 μg/ml for both H37Rv and wild strain but rifampicin hardly showed any activity on TMC-331. The MBC value for the methanol extract of L. camara was 30μg/ml for the H37Rv, and 20μg/ml for both the TMC-331 and wild strains of M. tuberculosis. The MBC for rifampicin was 2.0μg/ml for both H37Rv and the wild strain.
Keywords: Anti-mycobacterial; Medicinal plant; Lantana camara; Mycobacterium; tuberculosis